Symptoms and Treatment Needs of People with Dementia-Related Psychosis: A Mixed-Methods Study of the Patient Experience. Issue 3 (27th May 2022) - Brandt, Teresa; Frangiosa, Theresa; Biggar, Virginia; Taylor, Angela; Valentine, James; Keller, Bill; Price, Mark; DeMuro, Carla; Abler, Victor
ABSTRACT: Objectives: This study describes the person-centered experience and impact of symptoms and the treatment needs of dementia-related psychosis (DRP) from a patient and care partner perspective. Methods: Qualitative interviews and a quantitative survey were used to collect patient experience data from persons with DRP or their care partners. Results: Sixteen participants (1 person with DRP, 15 care partners) completed the qualitative interview; 212 participants (26 persons with DRP, 186 care partners) completed the quantitative survey. The most commonly reported symptoms were visual hallucinations, auditory hallucinations, persecutory delusions, and distortion of senses. The most common impacts were difficulty differentiating what is real from what is not real, increased anxiety, and effects on personal relationships. Current treatments were less than moderately helpful, and the ability to distinguish what is real from what is not real and overall symptom improvement were described as the most important benefits of an ideal treatment. Conclusions: Patient experience data provide insights into urgent therapeutic needs of patients by describing the nature, frequency, and severity of symptoms and the impacts they have on individuals' lives. Clinical Implications: Patient experience data demonstrate an unmet need for treatments to reduce the symptoms and impacts of DRP.